EKSISTENSI TRADISI MANDI SAFAR DI DESA TANJUNG PUNAK KECAMATAN RUPAT UTARA KABUPATEN BENGKALIS - Asbihani, Al; Jalil, Asaluddin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
The existence of the rural tradition of bathing safar Tanjung Punak Bengkalis District of North Rupat. The purpose of this study to Know the existence or the existence of the tradition of bathing safar annually and for mengertahui effort of people in keeping the tradition of bathing safar, tradition that has lasted for a long time to be conducted every year, precisely in the month of Safar Wednesday Recently within the Hijra year. Tradition bath Cape Punak safar village is dignity and a custom made by those who passed and should be preserved. safar bathing ritual has been made into a more modern, but does not leave a long tradition, in this modern era that most teenagers will not know again the tradition of bathing Safar if they are not given the knowledge about the importance of the ritual bath safar that every year they commemorate. Things like these are to be maintained and preserved that tradition become a habit of the people will not be left behind and forgotten. Keywords: Existence Tradition, effort Societ